Influence of stiffener configuration on post-buckled response of composite panels with impact damages - Masood, S. (2020)
In this paper, the effect of T, I and J stiffer configurations on post-buckling response of composite stiffened panels with impact damage is investigated through experiments and numerical simulations. Two identical panels in all three configurations were designed and manufactured. Each panel has four stringers of the same type. All panels were designed to have a skin buckling load of 92 kN ± 5 kN and weight of 1.45 kg ± 0.05 kg to separate the effect of impact damage irrespective of stiffener type. One panel from each configuration is impacted with 50 J energy above stiffener flange from skin side to create a Barely Visible Impact Damage (BVID) and followed by a compression test till collapse. A comparative study between pristine and impacted panels is presented. The effect of impact damage on buckling load, post-buckling response, collapse load and end-shortening were investigated. Moreover, finite element numerical models were developed for all panels which include intra-laminar and inter-laminar damage initiation and growth models. Impact damage area measured from ultrasonic C-scan was modelled in commercial finite element software Abaqus®. Failure modes in pristine and impacted panels such as disbond, tearing of stiffener web and locations from experiments are discussed and validated by numerical simulations.